The Effect Of Combination Of Ginger And Honey Combination On Asthma Patients With Ineffectiveness Of Breath Pattern In Pujidadi Binjai Village In 2023 - Empraninta, Hanna Ester (CV. Devitara, 2024)
Asthma is a chronic disease that attacks the respiratory tract with marked shortness of breath due to narrowing of the airways. One of the non-pharmacological measures to reduce asthma is the administration of a combination of ginger and honey boiled water. The aim of the study was to identify the effect of consuming a combination of ginger and honey boiled water on asthma sufferers. This study uses a quasi-experimental research design approach with two groups pretest posttest. The sample of this study were 30 asthma patient respondents who were undergoing treatment which were divided into two groups, 15 intervention groups and 15 control groups. The sampling technique uses the Slovin formula. Research data collection used demographic data, informed consent sheets, Asthma Control Test (ACT) questionnaires, which were combined using a modified combination of ginger and honey boiled water. Data were analyzed using descriptive statistics, paired t test and independent t test. The results showed that there was an effect of consuming a combination of ginger and honey boiled water on ineffective breathing patterns, post-test intervention group (t = -23,503, p=0,001) and post-test control group (t = -5,281; p=0,001) and there was a significant difference significantly to the ineffectiveness of breathing patterns between the post-test of the intervention group and the post-test of the control group after the intervention was carried out by consuming a combination of ginger and honey boiled water for ineffective breathing patterns, the intervention group and the control group after filling out the Asthma Control Test (ACT) questionnaire obtained a value (t = 4,707, p=0,001). The results of this study can recommend consuming a combination of ginger and honey boiled water as a non-pharmacological measure to help reduce the ineffective breathing pattern of asthma sufferers.